Aerial Digital Archaeology and Data Ethics through the Lens of Actor-Network Theory - Ros, Sayumphu (Wydział Filozoficzny UAM, 2025)
Actor-network theory emphasizes the importance of technology in archaeological research, particularly in aerial digital archaeology. It deconstructs objective narratives by revealing the complexity of knowledge production, including the archaeologist’s expertise, excavation tools, technology, and the researcher’s cultural background. Data are a dynamic output of the network, influenced by factors like tools, environment, and survey timing. The researcher’s cultural context also plays a role, as Western archaeologists may have different approaches and interpretations from those of researchers from developing countries. The theory also highlights the power dynamics of the network, with those controlling it – through technology, funding, and interpretation – wielding greater influence. This raises ethical concerns, especially in cases of “parachute science”, where foreign researchers conduct research in developing countries. A strong ethical framework is therefore needed to address these issues, and to promote collaboration and knowledge transfer. Actor-network theory encourages a more collaborative, ethically sound approach to understanding the past, especially when using aerial digital archaeology. This article systematically argues for such an approach.
Keywords: Actor-Network Theory; research ethics; aerial digital archaeology; parachute science; Power Dynamics